Human component of knowledge management for innovation in institutions of higher learning: a literature review - Ibrahim, Mohamed; Aliyu Olugbenga, Yusuf; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
This paper tries to find out and clarify the role of human in knowledge management in institutions of higher learning as regards to innovation. This paper seeks to describe, recognize and classify the key drivers for application of knowledge management in innovation for higher institution. It also details the nature of the role of knowledge workers (human component) in innovation as well as its value proposition. The methodology used was literature research and the findings indicated that innovation has become the mainstay of organizations including institutions of learning.